2018
DOI: 10.1038/s41389-017-0017-3
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic potential of targeting S100A11 in malignant pleural mesothelioma

Abstract: Malignant pleural mesothelioma (MPM) is an aggressive tumor with an unfavorable prognosis. The standard therapeutic approaches are limited to surgery, chemotherapy, and radiotherapy. Because the consequent clinical outcome is often unsatisfactory, a different approach in MPM treatment is required. S100A11, a Ca2+-binding small protein with two EF-hands, is frequently upregulated in various human cancers. Interestingly, it has been found that intracellular and extracellular S100A11 have different functions in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 33 publications
2
5
0
Order By: Relevance
“…Consistent with our findings in ER+ breast cancer cells, previous studies have shown that S100A11 is heterogeneously expressed in solid tumors [31,32]. Overexpression of S100A11 in cervical cancer cells increases their proliferative and migratory abilities [23].…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with our findings in ER+ breast cancer cells, previous studies have shown that S100A11 is heterogeneously expressed in solid tumors [31,32]. Overexpression of S100A11 in cervical cancer cells increases their proliferative and migratory abilities [23].…”
Section: Discussionsupporting
confidence: 92%
“…The dysregulation of S100A11 is linked with oncogenic activities including cancer progression. It has been observed to be overexpressed in many human solid tumours, such as pancreatic, melanoma, breast, ovarian and colorectal cancer [30][31][32][33][34]. Here we propose S100A11 may play a positive role during the development and progression of GC.…”
Section: Discussionmentioning
confidence: 70%
“…Over the last 3 years, additional insights into the multiple implications of this protein in the EMT process have been provided, such as its interaction with annexin A2 (Tu et al, 2019), its contribution to higher stiffnessinduced mesenchymal shifts through its membrane translocation (Dong et al, 2019), and its participation in multiple signaling pathways, including MAPK3 (ERK1), phosphatidylinositol-4,5-bisphosphate 3-kinase catalytic subunit alpha (PIK3CA), HGF/ MET, cyclic adenosine monophosphate response element binding protein (CREBBP) and MMP9 (Cui et al, 2021). Finally, the decrease in S100A11 abundance produced by curcumin treatment in our studies in vivo may open up interesting prospects as the only previous published works on this protein in MM reported active secretion of S100A11 by mesothelioma cells in vitro (Saho et al, 2016), while its neutralization by an anti-S100A11 antibody inhibited the proliferation of pleural MM cells in vitro and in vivo (Sato et al, 2018).…”
Section: New Insights From Malignant Mesothelioma Studiesmentioning
confidence: 65%